Sustainable Supply Chain Management and Inter-Organizational Resources: A Literature Review - Gold, Stefan; Seuring, Stefan; Beske, Philip (My University, 2010)
On the basis of a content analysis, this paper explores the role of sustainable supply chain management as a catalyst of generating valuable inter-organizational resources and thus possible sustained inter-firm competitive advantage through collaboration on environmental and social issues. Drawing on the resource-based view and its extension, the relational view, this paper highlights that partner-focused supply management capabilities evolve to corporate core competences as competition shifts from an inter-firm to an inter-supply chain level. The ‘collaborative paradigm’ in supply chain management regards strategic collaboration as a crucial source of competitive advantage. Collaboration is even more essential when supply chains aim at ensuring simultaneously economic, environmental and social performance on a product’s total life-cycle basis. Inter-firm resources and capabilities emerging from supply-chain-wide collaboration are prone to become sources of sustained inter-firm competitive advantage, since they are socially complex, causally ambiguous and historically grown and hence particularly difficult to imitate by competitors.
Keywords: sustainable supply chain management; sustainable development; inter-organizational resources; resource-based view; case studies; literature review.